Agent-Based Simulation of School Choice in Bandung, Indonesia: The Emergence of Enrolment Pattern Trough Individual Preferences - Utomo, Dhanan Sarwo; Putro, Utomo Sarjono; Hermawan, Pri (The Asian Journal of Technology Management (AJTM), 2009)
This study is motivated by the reality that school choice programs that is currently implemented in Bandung that, always resulting student deficit (lack of student) in some schools. In this study, a mechanism that can describe how the enrollment pattern in a school choice program emerge as a result of individual preferences of the prospective students, is constructed. Using computer simulation, virtual experiments are conducted. In these experiments, the enrollment patterns and the number of student deficit that were resulted by various school choice program configurations are analyzed. Based on the experiment results, modification of the current program that can minimize the number of student deficit can be purposed.Keywords: agent-based simulation, school choice, computer simulation